FORMS OF ADULT EDUCATION IN THE CONDITIONS OF INFORMAL EDUCATION - Oleksin, Yurii; Alla, Volodymyrivna; Valentina, Anatolyivna; Tamara, Evgenivna; Yakubovska, Svitlana (Sworld-Us Conference proceedings, 2023)
The article highlights the forms of education for adults in the conditions of non-formal education.